ӨЗБЕКСТАН РЕСПУБЛИКАСЫНДАҒЫ ҮЗЛИКСИЗ КӨРКЕМ-ПЕДАГОГИКАЛЫҚ БИЛИМЛЕНДИРИҮ - Уразимова, Т.В. (ILIM hám JÁMIYET, 2019)
The article is devoted to the modern content and role of the educational process, because in modern society much attention is paid to the problem of continuous artistic education. The aesthetic education plays here an important role contributing to enhance the development of word view, intellectual and creative potential of the individual. Therefore, the process of education should be based on creating conditions for education of creative personality, ready for a dialogue, collaboration and co-creation in various spheres of life.